The Role of Play in the Socialization of Children - Şen, Burcu Gezer (Mustafa Süleyman ÖZCAN, 2025)
Although there is a consensus that play has positive effects on children's development, learning and socialization, it is extremely difficult to define play. There are many questions to be asked about play, such as what play means, the essence of play, the limits of play, the effects of play on socialization, or what children learn from play. Play has long been valued in early childhood education. The role of play in the healthy development, learning and socialization of children continues to be investigated. Play research covers a wide area. Play is a broad concept that expresses various activities and experiences that can be observed in individuals of all ages. In addition, play is a universal concept. Almost every child plays games all over the world. Play has been accepted as the fundamental right of every child. According to many thinkers, play is the child's work. The play itself is an important goal; it is also a tool for other purposes. Play can be seen as a natural means by which young children learn. Children playing games build their personal and social identities as well as gaining knowledge about the world. Play is a way for children to learn about their own culture and societal expectations. Through play, children observe, experience and internalize how they should behave in society. Play is an important and critical part of the development of all children. All areas of children's development are intricately intertwined. Play benefits each of these areas of development in direct and indirect ways. Play begins in a child's infancy and ideally continues throughout his life. In this study, it is aimed to examine the role of play in the social life of the child. For this purpose, the concept of play, the role of play in the socialization of the child and the role of play in the education of the child are discussed. In the content of the study, the literature on the basic concepts, approaches and sociological dimension of the play is mentioned.

Oyunun çocukların gelişimi, öğrenmesi ve sosyalleşmesi üzerinde olumlu etkileri olduğuna dair fikir birliği olmasına rağmen oyunu tanımlamak son derece güçtür. Oyunun ne anlama geldiği, oyunun özü, oyunun sınırları, oyunun sosyalleşmeye etkileri veya çocukların oyunlardan neler öğrendiği gibi oyunla ilgili sorulacak birçok soru söz konusudur. Erken çocukluk eğitiminde oyuna uzun süredir değer verilmektedir. Oyunun çocukların sağlıklı gelişimi, öğrenmesi ve sosyalleşmesindeki rolü araştırılmaya devam etmektedir. Oyun araştırmaları geniş bir alanı kapsar. Oyun, her yaştan bireyde gözlemlenebilen çeşitli etkinlikler ve deneyimleri ifade eden geniş kapsamlı bir kavramdır. Ayrıca oyun, evrensel bir kavramdır. Hemen hemen her çocuk, dünyanın her yerinde oyun oynar. Oyun her çocuğun temel hakkı olarak kabul edilmiştir. Birçok düşünüre göre oyun çocuğun işidir. Oyun başlı başına önemli bir amaçtır; aynı zamanda başka amaçlar için bir araçtır. Oyun, çocukların öğrendiği doğal bir araç olarak görülebilir. Oyun oynayan çocuklar, dünya hakkında bilgi edinmenin yanı sıra bireysel ve sosyal kimliklerini de inşa etmektedir. Oyun, çocukların kendi kültürleri ve toplumsal beklentiler hakkında bilgi edinmelerinin bir yoludur. Oyun sayesinde çocuklar toplumda nasıl davranmaları gerektiğini gözlemler, deneyimler ve içselleştirir. Oyun, tüm çocukların gelişiminin önemli ve kritik bir parçasıdır. Çocukların gelişiminin tüm alanları karmaşık bir şekilde iç içedir. Oyun, bu gelişim alanlarının her birine doğrudan ve dolaylı yollarla fayda sağlar. Oyun, çocuğun bebeklik döneminde başlar ve ideal olarak yaşamı boyunca devam eder. Bu çalışmada, oyunun çocuğun sosyal hayatındaki rolünün incelenmesi amaçlanmıştır. Bu amaç doğrultusunda oyun kavramı, oyunun çocuğun sosyalleşmesindeki rolü ve oyunun çocuğun eğitimindeki rolü konuları ele alınmıştır. Çalışmanın içeriğinde oyunun temel kavramlarına, yaklaşımlarına ve sosyolojik boyutuna ilişkin alanyazına değinilmiştir.
Çocuğun Sosyalleşmesinde Oyunun Rolü
Keywords: Other Fields of Education; Alan Eğitimleri